PELATIHAN PUBLIC SPEAKING DAN PERSONAL BRANDING DI SMA SANTA MARIA YOGYAKARTA - Pramusiwi, Aloysia Desy; Adyantari, Api; Budiyono, Elizabeth Fiesta Clara Shinta; Sasmita, Raymundo Patria Hayu; Pradana, Bartolomeus Galih Visnhu; Putra, Tegar Satya; Mayasari, Agatha; Aji, Mario Rosario Wisnu; Pratama, Yohanes Mario; Dharomesz, Vonezyo Yupanzara (Jurnal Pengabdian Masyarakat Berkarya, 2024)
This community service activity aims to provide knowledge and develop abilities, as well as motivate high school students in terms of public speaking and self-imaging. This community service activity was carried out at Santa Maria High School Yogyakarta. The method of implementation is collecting initial data, analyzing problems, formulating solutions, and implementing training with a focus on improving the soft skills of the students. The results of this service, the school was very welcomed, and the students participated in the training and mentoring with great enthusiasm. As a result, the students consider that public speaking skills are important to master from an early age because these skills have many crucial benefits for their personal and professional development. Not only that but building their personal branding as early as high school is useful for positively establishing their own identity and reputation, as well as preparing them for a future in the competitive world of work. Having a good self-image can give students a leg up in securing scholarships, college places, or jobs.